Polyoxometalates‐Modulated Hydrophilic‐Hydrophobic Composite Interfacial Material for Efficient Solar Water Evaporation and Salt Harvesting in High‐Salinity Brine - Cheng, Sihang; Liu, Cuimei; Li, Yingqi; Tan, Huaqiao; Wang, Yonghui; Li, Yangguang (Energy & environmental materials (Hoboken, N.J.), 2024)
Solar vapor generation (SVG) represents a promising technique for seawater desalination to alleviate the global water crisis and energy shortage. One of its main bottleneck problems is that the evaporation efficiency and stability are limited by salt crystallization under high‐salinity brines. Herein, we demonstrate that the 3D porous melamine‐foam (MF) wrapped by a type of self‐assembling composite materials based on reduced polyoxometalates (i.e. heteropoly blue, HPB), oleic acid (OA), and polypyrrole (PPy) (labeled with MF@HPB‐PPyn‐OA) can serve as efficient and stable SVG material at high salinity. Structural characterizations of MF@HPB‐PPyn‐OA indicate that both hydrophilic region of HPBs and hydrophobic region of OA co‐exist on the surface of composite materials, optimizing the hydrophilic and hydrophobic interfaces of the SVG materials, and fully exerting its functionality for ultrahigh water‐evaporation and anti‐salt fouling. The optimal MF@HPB‐PPy10‐OA operates continuously and stably for over 100 h in 10 wt% brine. Furthermore, MF@HPB‐PPy10‐OA accomplishes complete salt‐water separation of 10 wt% brine with 3.3 kg m−2 h−1 under 1‐sun irradiation, yielding salt harvesting efficiency of 96.5%, which belongs to the record high of high‐salinity systems reported so far and is close to achieving zero liquid discharge. Moreover, the low cost of MF@HPB‐PPy10‐OA (2.56 $ m−2) suggests its potential application in the practical SVG technique. Benefiting from the hydrophilic–hydrophobic engineering and the unique structure of the surface, 3D porous MF@HPB‐PPy10‐OA yields an impressive evaporation rate of 3.3 kg m−2 h−1 and a salt harvesting efficiency of 96.5% in desalination of 10 wt% brine.